Prediction of clinical outcomes of single- and double-bundle anterior cruciate ligament reconstruction techniques using magnetic resonance imaging - YAPICI, ÖZGE (My University, 2021)
BACKGROUND: The objective of the study is to compare the clinical results of the single-bundle (SB) and double-bundle (DB) anterior cruciate ligament (ACL) repairing techniques using magnetic resonance imaging (MRI).
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Anterior cruciate ligament; double-bundle; magnetic resonance imaging; single-bundle; SEMITENDINOSUS TENDON; ACL RECONSTRUCTION